An observation account from EFL/ESL dyads: code-switching and willingness to communicate - Amirkhiz, Seyed Yasin Yazdi; Abu Bakar, Kamariah (Australian International Academic Centre, 2014)
This paper reports a small part of the findings of a larger study which cross-culturally explored and comparatively examined the dynamics of collaboration between Iranian and Malaysian homogeneous dyads during performing collaborative writing tasks. The findings related to the amount of code-switching as well as the amount of falling back on the researcher for language-related assistance in each of the dyads are reported. It was found that while resorting to L1 and willingness to communicate with the researcher was next to nothing in Malaysian dyads, the Iranians had a considerably higher tendency towards using their own language and referring to the researcher for language-related help. The findings are discussed in relation with the previous findings in the related literature.